Respostas

2014-06-10T17:04:21-03:00
1º)
a) 14/3 + 3/8 = [(8.14)+(3.3)]/24 = 121/24

b) -6/5 - 8/3 = [(-6.3)-(8.5)]/15 = -58/15

c) -9/4 : 3/8 = -9/4 . 8/3 = -4
...........
2º)
a) a³.a² = a³⁺² = a⁵

b) 2².2² = 2²⁺² = 2⁴ = 16

c) 4³.4 = 4⁴⁺¹ = 4⁵ = 1024
............
3º)
a) (7y³-2y²+3y-5) + (y³-4y+9) - (5y³+4y²-y+1) = 7y³-2y²+3y-5+y³-4y+9-5y³-4y²+y-1 = 
= 7y³+y³-5y³-2y²-4y²+3y-4y+y-5+9-1 = 3y³ - 6y² +3 = 3(y³-2y²+1)

b) (2a+b)(a-b) = 2a² - 2ab + ab - b² = 2a² - ab + b²

c) 35a²x³ - 20a³x²(5a²x) = 5a²x(7x-20a³x²)
..............
4º)
a) √4√2√3 = 2√(2.3) = 2√6

b) √6√7√1 = √6√7 = √(6.7) = √42
  • Usuário do Brainly
2014-06-10T17:17:00-03:00
 \frac{14}{3}  +  \frac{3}{8} =  \frac{112 +9}{24} =  \frac{121}{24} 

 

 



 \frac{-6}{3} - \frac{8}{3} =  \frac{-18-40}{15} =  \frac{-58}{15}


 \frac{-9}{4} :  \frac{3}{8}  =  \frac{-9}{4} .  \frac{8}{3} = \frac{-72}{12} =-6



2)  a^{3} . a^{2} = a^{5} 

 2^{2} .  2^{2} = 2^{4} 

 4^{3} .4 = 4^{4}


3)  7y³+y³+ 5y³- 2y²- 4y²+3y-4y+y-5+9-1=
  
   13y³-3y³ +3

b) 2a²-2ab+ab-b²=2a²-ab -b²

c)  7x²- 4ax